Anticorrosion Behaviour of Zenthoxylum alatum Extract in Acidic Media - Singh Chauhan, Jinendra (Asian Journal of Chemistry, 2010)
The commercial non-ionic surfactant plant used as a medicine, namely Zenthoxylum alatum were tested as inhibitors for the corrosion of copper and aluminium in 0.1 M solution of HCl. Weight loss measurement and potentiometry polarization technique were used in this study. It was found that this compound acts as a good inhibitor for the acid corrosion of copper and aluminium. the inhibition efficiencies obtained by the two technique were almost the same, and increased with the increasing the concentration of inhibitors. The polarization technique shows that the compound acts as an inhibitor. The inhibition action of the surfactant is interpreted in view of the adsorption on the metal surface making a barrier to mass and charge transfer. It was found that the adsorption of the compound follows Langmuir adsorption isotherm. The values of free energy of adsorption for them were calculated. It was found that the adsorption process is spontaneous and increases, for the different surfactant, in the same direction as inhibition efficiency.